INTEGRAL SEMES OF THE LEXICAL SEMANTIC FIELD MODAL WORDS RELIABILITY INDICATORS (Web of Teachers: Inderscience Research, 2024)
The given article is devoted to the Integral semes of the lexical-semantic field modal words - reliability indicators. This paper explores the potential of exploiting integral semes, which are the inherent meaning components, within the lexical-semantic field of modal words for enhancing reliability assessment in natural language processing.